MICROSTRUCTURAL MAPPING OF THE AUSTENITIC MANGANESE STEEL-3401 IN RAPID COOLING PROCESS - Siregar, Riski Elpari; Fadhila, Reza (JURNAL PENELITIAN SAINTIKA, 2011)
Hadfields austenitic manganese steel which contained approximately 1.2% carbon and 12 tol4% Mn is still commonly used for railroad components such as frogs and crossings and also for rock-handlingmaterials. This paper presents the microstructural development of the austenitic manganese steel-340 Idue to different heating regimes followed by rapid cooling process. The material is heated to l 050°Cfollowed by a rapid cooling process which caused the solid solution of the carbides to be precipitatedin the grain of the pure austenite phase. The tempering temperature is set between 400°C to 600°C at50° C interval. The microstructural examination of the samples showed that the formation of austenitebegins by precipitation of iron and manganese carbides at the grain boundaries, progressively followed by the appearance of a new constituent which later extended to the interior of the grains. The newphase formation increased with increasing temperature, showing temperature dependence of formation.